Cardiovascular diseases in the elderly – diagnostic difficulties and distinction of pharmacotherapy - Gryglewska, Barbara (Przewodnik Lekarza/Guide for GPs, 2007)
The present article describes diagnostic and management patterns of arterial hypertension, coronary artery disease, congestive heart failure, selected dysrythmias and valvular heart diseases according to current guidelines and literature. Diagnostic procedures are difficult in the elderly because of atypical manifestations of cardiovascular diseases and interactions between age-associated changes and pathophysiologic mechanisms of the diseases. Management patterns based on scientific societies’ guidelines are not different from those recommended to younger patients. However, it is important to remember about increased responses to medications in older age and the necessity of dose modification. Results of the studies in the elderly confirm the benefits of invasive treatment of coronary artery disease and valvular diseases.